Harmonic gradations in the third movement of the String Quartet n. 2 by György Ligeti : the reevaluated concept of micropolyphony (Per Musi, 2022)
From Lacrimosa (Requiem) Ligeti modifies his language as he gradually leaves the cluster's harmony. He starts inserting holes in the texture and using a smaller number of instruments. This attitude implies a reassessment of the micropolyphony technique (used in his previous sound mass works) and an adaptation of this texture to the new context. For perception, the consequences of these changes are evident; this makes it possible to hear many details of the sound that were submerged in the sound fabrics of works such as Apparitions, Atmosphères, and Requiem. Our analysis shows how this process takes place in the third movement of his String Quartet No 2. We base our study on the idea that the concept of gradation serves as a central element in the construction of music.